Prevalence of obesity and acanthosis nigricans among young children in the children's healthy living program in the United States Affiliated Pacific. Issue 37 (September 2016) - Novotny, Rachel; Li, Fenfang; Fialkowski, Marie Kainoa; Bersamin, Andrea; Tufa, Aifili; Deenik, Jonathan; Coleman, Patricia; Guerrero, Rachael Leon; Wilkens, Lynne R.; ,
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Estimate prevalence of obesity and acanthosis nigricans (AN) among children in United States Affiliated Pacific (USAP) jurisdictions. Cross-sectional measurement of weight, height, and AN in 5775, 2 to 8 years old in 51 communities—Hawai'i, Alaska, Commonwealth of the Northern Mariana Islands, Guam, American Samoa, Palau, Republic of the Marshall Islands (RMI), 4 Federated States of Micronesia (Pohnpei, Yap, Kosrae, Chuuk). Analyses weighted to jurisdiction-specific sex and age distributions accounting for clustering of communities within jurisdictions. Prevalence of obesity was 14.0%, overweight 14.4%, healthy weight 68.9%, and underweight 2.6%, higher in males (16.3%) than females (11.6%), higher among 6 to 8 years old (16.3%) than 2 to 5 years old (12.9%), highest in American Samoa (21.7%), and absent in RMI. In total, 4.7% of children had AN, with no sex difference, higher in 6 to 8 years old (6.8%) than 2 to 5 years old (3.5%) and highest in Pohnpei (11.9%), and absent in Alaska. Obesity was highly associated with AN (odds ratio = 9.25, 95% confidence interval = 6.69–12.80), with the strongest relationships among Asians, followed by Native Hawaiians and Pacific Islanders (NHPI). Obesity, age, and Asian and NHPI race were positively associated with AN.